Penerapan Program Asuransi Karyawan sebagai Strategi Mitigasi Risiko dan Peningkatan Kesejahteraan di Bank Rakyat Indonesia (BRI) - Ciska Silvi Oktavia; Lollita Apriliani; Lutvia Nida; William Setiawan (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Employee welfare and risk management are two crucial aspects in the sustainability of modern banking operations. In the midst of economic and social, Bank Rakyat Indonesia (BRI), one of the largest financial institutions in Indonesia, faces challenges to maintain human resource productivity. Using quantitative methods, this study investigates the implementation of employee insurance programs as a way to reduce risk and improve welfare in the BRI work environment. The study population was all permanent employees of BRI. The results showed that employee insurance programs increased employee satisfaction and reduced work risks. The novelty of this study lies in the integrative method that combines elements of employee welfare and risk mitigation for national banking institutions. The implications of these findings indicate that a well-planned insurance program not only serves as protection, but can also increase employee loyalty and productivity. This study is expected to contribute to the policy-making process related to human resource management sources in the Indonesian banking sector.